Evaluasi Uji Hedonik dan Uji Iritasi Sediaan Lotion Minyak Atsiri Daun Cengkeh (Eugenia Aromatic L.) - Fitri Kurniasari (Fakultas Farmasi Universitas Setia Budi, 2016)
Clove (Eugenia aromatic L.) is one of the natural subtances that can be used to natural repelan with the biggest metabolite compound eugenol. This study was to determine the quality standardization of clove leaf essential oil compounds and their components. This study aimed to evaluated the lotions hedonic test and lotions irritation test. Essential oil was obtained by water and steam destillation then analyzed the levels of compounds clofe leaf with GCMS method. Essential oils are used in the preparation obtained lotion with a concentration of 1% (F1), 3% (F2), 5% (F3) and 7% (F4). Observations were done on the organoleptic test, i.e. color, smell, homogeneity, irritation, pH, viscosity, protection ability and hedonist test of formulas Test repelan activity of essential oil. Test data in statistical analysis by one-way ANOVA with a level of 95%. The research shows that standardization in the clove leaf essential with hedonic test of the clofe leaf essential oil concentration of 7% (F4), with and no irritation reported.